Sosialisasi Penjas Adaptif Melalui Permainan Edukatif Scooter Board di SDLB YPAC Palembang - Hardiyono, Bayu; Taroreh, Bangkit Seandi; Kesumawati, Selvi Atesya; Fikri, Aprizal; Sukmawati, Noviria; Martinus, Martinus; Vrananda, Aidy Viktor (Abdibaraya, 2023)
Optimization of understanding of adaptive PE through scooter board educational games in the community is not optimal so efforts are needed to overcome it, one of which is through outreach activities. Community service activities are carried out at SDLB YPAC Palembang with three stages including: 1) planning, 2) implementation and 3) evaluation. Data collection techniques through observation. Data analysis techniques using quantitative analysis. Community service subjects totaled 23 people. The conclusion of community service is that there is an increase in understanding by 100% (23 people). During the implementation of this activity students look happy, cheerful, show curiosity. Keywords: adaptive physical education, scooter board educational games